If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Oblicz to!
y-(-x)^2-5;y-(-2*x)-2
x^2-(2*x) = 0
y-(-x)^2-5;y-(-2*x)-2
1/1-(2*e^x)-1
(7*a)/2 = 5*a-3
| 5-29=4z | | 3.4x=-6.6 | | 4w+6=4(w+3)-13 | | 5z^2+12z+7= | | 3x-4x^2=-25 | | 4(n+5)-5(2n-1)=n-24 | | 2(cosx)^3-cosx-(√3/4)=0 | | 8a+1+25=356 | | 8a+1+25=35635 | | 6x^8z^3+48x^5=0 | | 4x=-15y-17 | | 4x=-15-17 | | 7a/2=5a-3 | | 15*12-16*N=967 | | -2.2+(-1.9)= | | R=9 | | 6(v)=6v+15 | | Y+y-10y+21=0 | | Y+y-10y+121=0 | | -15x+35=25 | | 7x^2-8x-4=-10x | | 7(3n-1)-2(2n+3)=14 | | 3m+21=6m-3 | | 6m+10=8m-4 | | y=2x-1.5 | | 25k-3(8k-4)=16k-4 | | 2x-12=34 | | -2.9(-4y-3)+2.1y= | | g+28=13g-8 | | (4z+9)(1+z)=0 | | 2sin(2x)=2(sinx) | | (2cosx-1)(cosx+1)=0 |